Pengembangan Media Pembelajaran Interaktif pada Materi Sistem Persamaan Linear Dua Variabel - Chandra Kusuma Hadi Putra; Atik Wintarti; Nina Rinda Prihartiwi (MATHEdunesa, 2023)
This study aims to develop interactive learning media based on PowerPoint VBA on a system of two-variable linear equations and determine the results of the development of learning media in terms of validity, practicality, and effectiveness. This research uses the ADDIE development model. The instruments used included media validation sheets for media experts, media validation sheets for material experts, pretest-posttest sheets, student and teacher observation sheets, and user response questionnaire sheets. Based on the results of the research that has been done, an average validity value of 3.08 (media expert) and 3.29 (material expert) is obtained so that it can be categorized that PowerPoint VBA-based interactive learning media is valid. This learning media trial was conducted on a limited basis to 25 class VII students of SMP Negeri 1 Dlanggu to obtain data from practicality (student observation sheets, teacher observation sheets, and user response questionnaires) and media effectiveness (pretest and posttest). The results of the study after being tested and evaluated, that this learning media is said to be practical because based on the percentage of user response questionnaires obtained 75.75% or it can be used without revision and based on student and teacher observation sheets each obtained a very good category with a percentage of 93.68 % and 78.57%. Based on the pretest and posttest with an N-Gain value of 0.37, it can be said that this PowerPoint VBA-based interactive learning media is effective in the moderate category.